THE INFLUENCE OF STAD TYPE COOPERATIVE LEARNING MODEL ON HEAT MATERIAL AND ITS TRANSFER ON CRITICAL THINKING ABILITY AND SCIENCE LEARNING OUTCOMES - Yulia Rahmawati; Sutarto Sutarto; Nur Ahmad (Universitas Bhinneka PGRI, 2024)
The development of education is marked by advances in science and technology which cause every individual to have the ability